179 Using a traffic light system to identify palliative care needs in adult neuromuscular patients. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Willis, Derek; Vithlani, R; Willis, Tracey
Abstract : The Department of Health has made a commitment to provide personalised and coordinated palliative and end of life care to those with life limiting conditions. Many neuromuscular diagnoses are or have the potential to be life limiting. Internationally there has been a lack of palliative service involvement or palliative approach to patients with such conditions. Recognising that this was true of our neuromuscular service, we used quality improvement to develop a more proactive approach. As part of this project we developed a traffic light system based on 'The Spectrum of Children's Palliative Care Needs' used in paediatrics. This was adapted to be more relevant for neuromuscular patients. By reviewing their respiratory, cardiac, locomotor and gastrointestinal status and their recent hospital admissions patients are allocated a colour. Most importantly 'it would not surprise' the clinician if those who were 'red' died within twelve months or 'amber' patients died within a few years. 'Green' patients are currently stable and for 'blue' patients their condition is not expected to be life limiting. This tool would identify where patients were in their disease progression and highlight those who might benefit from a palliative approach, discussing advanced care planning or being seen in our newly established symptom control clinic. All our patients with a palliative or potentially palliative diagnosis were allocated a traffic light colour and a system was developed to regularly review this. We used this to prioritise those patients with the most pressing need and consider how to best meet their needs. Figures for this will be available when the poster is published. It was not available as a full year of MDTs had not been run until the moment when late breaking was announced.